A NEW ORDER OF HETEROSPOROUS PLANTS FROM THE LATE CRETACEOUS OF THE KEM' RIVER, WESTERN SIBERIA - Krassilov V.A.; Golovneva L.B. (My University, 2000)
Remains of a heterosporous plant from the Late Cretaceous of the Tchulymo-Yenisey Basin, Western Siberia, are peculiar in having solitary sporangia on the laminar sporophyll pinnules. The sporangia produce a large number of megaspores in the symmetrically developed tetrads. Microspores are enveloped in the laesural outgrowths of the megaspores. These characters substantiate a new order of pteridophytes representing a special direction in the evolution of heterospory.
Keywords: Cretaceous; Mesozoic::Cretaceous; Мезозой::Меловая